How to Foster Inclusive Practice in Research Methods Teaching - Meredith Wilkinson; Zeynep Barlas; Jonathan Farnell; Olivier de Condappa (Studies in Empowering Education)
This paper outlines a practical approach to foster inclusive practice in research methods teaching. To achieve this, we follow the principles of Universal Design for Learning for our framework. We present four ways in which educators can make university research methods teaching more inclusive. These are: (1) make use of multiple modes of teaching, (2) integrate research methods into the curriculum rather than as stand-alone modules, (3) make assessments flexible and innovative, and (4) promote accessibility and effective use of digital tools and computer software. We draw upon our own experiences as research methods tutors and previous research to elucidate our points. This paper provides practical guidance for those teaching research methods to create more inclusive and equitable learning environments. Please note that our experience comes from teaching Psychology, which is what we base our case study on, but our discussion can be applied to a range of subject areas.